DEVELOPMENT OF INTERACTIVE E-LKPD BASED ON THE WIZER.ME WEBSITE FOR FLUID MATERIAL TO IMPROVE THE SELF-EFFICACY OF HIGH SCHOOL STUDENTS - Sindi, Sindi Nova Eliza; Purwanto, Andik; Koto, Irwan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study aimed to develop an interactive web-based e-LKPD using Wizer.me on fluid topics and to examine its eligibility , students’ responses, and effectiveness in enhancing high school students’ self-efficacy. A research and development approach based on the ADDIE model was employed. Product eligibility was evaluated through expert validation, while students’ responses and self-efficacy were measured using questionnaires. The results showed that the developed e-LKPD was categorized as Very eligibility, with an average validity score of 97.69%, and received very good student responses, with an average score of 98.16%. Furthermore, students’ self-efficacy significantly improved, indicated by a high N-Gain score of 0.92. In this study, the term deep learning is used in a pedagogical context to refer to meaningful, reflective, and conceptually integrated learning, rather than to machine learning. The novelty of this research lies in the systematic integration of Problem-Based Learning and a pedagogical deep learning approach within a Wizer.me-based e-LKPD specifically designed to enhance students’ self-efficacy in physics learning.